Human capital depreciation during family-related career interruptions in male and female occupations - Dennis Görlich; Andries De Grip (Kiel Institute for the World Economy (IfW), 2007)
This study investigates the relation between human capital depreciation during family-related career interruptions and occupational choice of women in the (West) German labour market. In contrast to other studies that do not explicitly focus on family-related career interruptions, we find that short-term human capital depreciation during these career interruptions is significantly lower in female occupations than in male occupations. This holds for both high- and low-skilled occupations. Our findings support the self-selection hypothesis with respect to occupational sex segregation, i.e., women might deliberately choose female occupations because of lower short-term wage penalties for family-related career interruptions. Moreover, we find that particularly men employed in high-skilled male occupations face large short-run as well as long run wage penalties when they have a family related career break.
Keywords: J24; J13; D13; 330; Occupational segregation; GSOEP; Parental leave; Skills obsolescence; Erwerbsverlauf; Humankapital; Bildungsertrag; Familie; Frauenerwerbstätigkeit; Männer; Vergleich; Deutschland